The Impact of Youth Risk on Mentoring Relationship Quality: Do Mentor Characteristics Matter?. Issue 3 (25th May 2016) - Raposa, Elizabeth B.; Rhodes, Jean E.; Herrera, Carla
Abstract: Although mentoring is a widely used intervention strategy, effect sizes for at‐risk youth remain modest. Research is therefore needed to maximize the impact of mentoring for at‐risk youth who might struggle to benefit from mentoring relationships. This study tested the hypothesis that different types of youth risk would have a negative impact on mentoring relationship quality and duration and explored whether mentor characteristics exacerbated or mitigated these negative effects. Results showed that elevated environmental stress at a youth's home and/or school predicted shorter match duration, and elevated rates of youth behavioral problems, such as poor academic performance or misconduct, predicted greater youth dissatisfaction and less positive mentor perceptions of relationship quality. Mentors with greater self‐efficacy and more previous involvement with youth in their communities were able to buffer the negative effects of environmental stress on match duration. Similarly, mentors' previous involvement with youth buffered the negative effects of youth behavioral problems on mentor perceptions of relationship quality. Findings have important implications for the matching of mentors and at‐risk youth in a way that improves mentoring outcomes.